2012
DOI: 10.1016/s0140-6736(12)61272-0
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of kidney disease measures with mortality and end-stage renal disease in individuals with and without hypertension: a meta-analysis

Abstract: Background Hypertension is the most prevalent comorbidity in individuals with chronic kidney disease (CKD). It is unknown, however, whether the association of the CKD measures, estimated glomerular filtration rate (eGFR) and albuminuria, with mortality or end-stage renal disease (ESRD) differs by hypertensive status. Methods We performed a meta-analysis of 45 cohorts (25 general population, 7 high-risk and 13 CKD cohorts), including 1,127,656 participants (364,344 with hypertension). Adjusted hazard ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
246
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(277 citation statements)
references
References 29 publications
13
246
0
9
Order By: Relevance
“…A step-wise relationship was demonstrated between worsening renal function (decreased eGFR, increased albuminuria) and all-cause mortality, cardiovascular mortality, and development of ESRD regardless of hypertensive status. 144 A similar study demonstrated an increased risk of ESRD and all-cause or cardiovascular death, regardless of whether or not a patient had a diagnosis of DM. 145 Decreased eGFR remained a strong risk factor for the development ESRD and death despite specifically controlling for HTN and DM.…”
Section: Ckd and Adverse Outcomesmentioning
confidence: 81%
“…A step-wise relationship was demonstrated between worsening renal function (decreased eGFR, increased albuminuria) and all-cause mortality, cardiovascular mortality, and development of ESRD regardless of hypertensive status. 144 A similar study demonstrated an increased risk of ESRD and all-cause or cardiovascular death, regardless of whether or not a patient had a diagnosis of DM. 145 Decreased eGFR remained a strong risk factor for the development ESRD and death despite specifically controlling for HTN and DM.…”
Section: Ckd and Adverse Outcomesmentioning
confidence: 81%
“…These observations are consistent with previous studies reporting a J-shaped association between serum creatininebased eGFR and mortality. [11][12][13][14][15][16][17] The J-shaped association between eGFR and mortality has been explained by the overestimation of the true GFR in individuals in the high-risk group because of muscle wasting. Previous studies defined high GFR as above a certain absolute value, irrespective of age, sex, and muscle mass, and could not exclude the possibility of the confounding effects of muscle wasting in the high-risk group or the misclassification of normal GFR in young subjects as higher GFR or higher GFR in older subjects as normal GFR.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased mortality associated with a higher GFR was commonly regarded as an overestimation of GFR because of muscle wasting in a high-risk group. [11][12][13][14][15][16][17] The disappearance of the J-shaped association between GFR and mortality within a younger age group in the higher GFR range is considered as supporting evidence for the overestimation of the true GFR …”
mentioning
confidence: 99%
“…Whilst the heterogeneity of these co-morbidities may potentially limit the findings of this meta-analysis, CKD remains a potent CV risk factor regardless of the presence or absence of DM or hypertension. This has been confirmed in large individual patient level meta-analyses in CKD compared to non- 18 CKD individuals for both all-cause and cardiovascular mortality and morbidity [24,25,26].…”
Section: Resultsmentioning
confidence: 64%